2449. Validation of In Vitro Activity of Aminoglycosides Against Recently Isolated Helicobacter pylori for Commercialization of Gentamicin-Intercalated Smectite Hybrid as a New Therapeutic Agent. (26th November 2018) - Lee, Kyoung Hwa; Park, Soon Young; Yoo, Seul Gi; Kwon, Da Eun; Jeong, Su Jin; Jung, Da Hyun; Kim, Jie-Hyun; Jeong, Seok Hoon; Kang, Il-Mo; Song, Young Goo
Abstract: Background: The eradication rate of Helicobacter pylori as a standard therapy based on amoxicillin and clarithromycin, exhibits a decreasing trend. Alternative approaches have been explored, but there is still controversy in the regimen change and these do not provide a satisfactory substitute to the existing standard therapy. Thus, a novel and efficient H. pylori eradication regimen should be developed. Smectite can serve as a drug delivery system and gentamicin-intercalated smectite hybrids (S-GEN) are expected to supersede the standard therapy for H. pylori eradication. In the previous study, we synthesized S-GEN complexes as a novel therapeutic agent. In a murine model, S-GEN released gentamicin to the gastric wall stably and the therapeutic effect was not inferior to the conventional standard therapy. The aim of this study was to confirm whether the minimum inhibitory concentration (MIC) of aminoglycosides applied as smectite hybrids remained low against recently isolated H. pylori strains. Methods: The H. pylori strains were collected via endoscopic biopsy from 1, 422 patients at Gangnam Severance Hospital in Seoul, Korea, between March 2015 and February 2018. Antimicrobial susceptibility tests were performed, and the MICs of eight antibiotics (amoxicillin, clarithromycin, metronidazole, tetracycline, levofloxacin, gentamicin, netilmicin, and tobramycin) were determined by using the Epsilometer test and following the European Committee on Antimicrobial Susceptibility Testing recommendations. Results: Finally, 140 H. pylori strains were analyzed in this study. The resistance rate to clarithromycin was 30.7%, although it is a major antimicrobial agent used in standard therapy. The MIC50 and MIC90 of gentamicin (MIC50 0.25 mg/L, MIC90 0.75 mg/L) and netilmicin (MIC50 0.19 mg/L, MIC90 0.75 mg/L) were lower than that of metronidazole, tetracycline and levofloxacin, which are alternative therapies for H. pylori eradication. In clarithromycin-resistant strains, the MIC50 was 0.25 mg/L and the MIC90 was 1 mg/L for gentamicin; for netilmicin, the values were 0.25 mg/L and 0.75 mg/L, respectively. Conclusion: Through the use of gentamicin and netilmicin, which have low MICs for H. pylori, aminoglycoside-intercalated smectite hybrids are expected to emerge as a new standard therapy for H. pylori eradication. Disclosures: All authors: No reported disclosures.